Sperm enter glands of preovulatory bovine endometrial explants and initiate inflammation. Issue 2 (February 2020) - Akthar, Ihshan; Suarez, Susan S; Morillo, Vernadyn A; Sasaki, Motoki; Ezz, Mohamed A; Takahashi, Ken-ichi; Shimada, Masayuki; Marey, Mohamed A; Miyamoto, Akio
Abstract : We previously reported that sperm binding to cultured monolayers of bovine uterine epithelial cells induces an acute inflammatory response involving the Toll-like receptor (TLR2) signaling pathway. This response serves to clear the uterus of sperm and thereby prepares the endometrium for implantation. The endometrium is lined by surface epithelial cells; however, epithelial cells also line uterine glands. To investigate the source of the immune response, we used an explant model. Explants of bovine endometrium were incubated with bull sperm illuminated by JC1 fluorescent labeling in their mitochondria. The sperm glided over the surface epithelium until they encountered and entered uterine glands, where they remained. Scanning electron microscopy of explants revealed polymorphonuclear neutrophils (PMNs) in uterine glands along with sperm. In the absence of sperm, PMNs were not seen in glands. The incubation of sperm with explants resulted in an acute inflammatory response, seen as the upregulation of mRNA expression of IL8, TNFA, IL1B, PGES and TLR2 in whole explants, as well as increased TNFA protein expression in uterine glands. TLR1/2 antagonist reduced sperm numbers in the glands and inhibited the increase of TNFA . Our observations suggest that uterine glands serve as a site where sperm interact with the uterine epithelium to trigger the innate immune response to clear excess sperm from the uterus.